2023
DOI: 10.3390/educsci13111131
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Filipino Online Learners: A Survey of Science Education Students’ Engagement, Self-Regulation, and Self-Efficacy

Mary Rose Briones,
Maricar Prudente,
Denis Dyvee Errabo

Abstract: Online education allows learners to develop knowledge and skills flexibly and conveniently—an observation made among students whose characteristics involve student engagement, self-regulation, and self-efficacy. However, studies characterizing Filipino online learners seem to be lacking. This study aimed to characterize science education tertiary students in the Philippines concerning their online student engagement (OSE), self-regulated learning (SRL), and online learning self-efficacy (OLSE). The unprecedent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Medina et al (2024) andEugenio et al (2024) recommend aligning teaching methods and communication styles with student preferences, particularly in remote learning environments. Customized communication approaches in scientific education must focus on engaging diverse learners and promoting selfregulation (Briones et al, 2023). Building emotional connection through communication is also a crucial aspect of fostering engagement.…”
Section: Instructor's Presence In Asynchronous Online Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina et al (2024) andEugenio et al (2024) recommend aligning teaching methods and communication styles with student preferences, particularly in remote learning environments. Customized communication approaches in scientific education must focus on engaging diverse learners and promoting selfregulation (Briones et al, 2023). Building emotional connection through communication is also a crucial aspect of fostering engagement.…”
Section: Instructor's Presence In Asynchronous Online Classmentioning
confidence: 99%
“…For instance, Gopez and Gopez (2023) examined the relationship between teacher scaffolding and self-regulation and suggested supportive relationships and the development of self-regulatory skills. On the other hand, Briones et al (2023) recommended tailored approaches to address diverse learner needs, focusing on online engagement, self-regulation, and self-efficacy while Garcia and Yousef (2022) concluded the importance of emotional connections and instructor support in boosting engagement. In terms of emotional well-being in influencing student engagement, Sandoval (2023) found that the higher levels of happiness correlate with greater engagement in both synchronous and asynchronous online classes.…”
Section: Student Engagement In Asynchronous Online Classmentioning
confidence: 99%